2002
DOI: 10.1080/02701367.2002.10609009
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity Patterns in Recent College Alumni

Abstract: Within this sample of recent college alumni, a high proportion indicated that they enjoy exercise (66.1%) and felt confident in setting their own fitness programs (79.4%). Yet, only 34.3% reported engaging in recommended levels of moderate or vigorous PA. In contrast to previous reports, rates of participation in vigorous, moderate, and strengthening-type PA did not differ between men and women. Alumni who reported that they engaged in adequate levels of moderate or vigorous PA had gained significantly less we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
106
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(110 citation statements)
references
References 9 publications
2
106
0
2
Order By: Relevance
“…Thus, it is important to gather information regarding factors that lead to physically active lives in male adolescents. Furthermore, research with adolescents is important because physical activity patterns established in adolescence can determine one's activity level throughout adulthood (Calfas, Sallis, Lovato, & Campbell, 1994;Sparling & Snow, 2002).…”
Section: Rationalementioning
confidence: 99%
“…Thus, it is important to gather information regarding factors that lead to physically active lives in male adolescents. Furthermore, research with adolescents is important because physical activity patterns established in adolescence can determine one's activity level throughout adulthood (Calfas, Sallis, Lovato, & Campbell, 1994;Sparling & Snow, 2002).…”
Section: Rationalementioning
confidence: 99%
“…For instance, Sparling and Snow (2002) revealed that 84.7% of the individuals who exercised regularly as college seniors were still physically active 5 or 10 years later after their graduation. Authors found the similar trend among those who were not active; 81.3% of the individuals who were physically inactive as college seniors sustained a sedentary lifestyle.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Sparling and Snow (2002) found that physical activity patterns during the senior year of college held for 6 years after graduation. Studies regarding college alumni also suggest that those who have participated in a larger numbers of physical activity courses while in college have better exercise habits and more positive attitudes toward fitness than do those who took fewer physical activity courses 6 to 20 years post-graduation (Adams & Brynteson, 1992;Brynteson & Adams, 1993;Pearman et al, 1997).…”
Section: Introductionmentioning
confidence: 99%